Strategy Study to Enhance the Value of Telecom Operators Based on Traffic Management——Empirical Analysis of S Corporation - Biao He; Mingguang Zhang; Lu Li (Dianxin kexue)
Rapid data traffic growth has led to operator data traffic grow while the income does not grow, network pressure increase, customer experience decline and so on. Operator has to mine customer needs and refine traffic management to avoid being only pipe in the mobile internet era, achieve a shift from the pipe to the bilateral market organizer, and enhance the value of telecom operator. S-provincial company of an operator was selected for the empirical case study. Through mining the information of current network user data, the traffic management status was analyzed. Further, combined with the benchmark study for traffic management both in technology and management, specific measures to enhance the value of telecom operators were proposed.